ISO 9000 نظام ادارة الجودة : دراسة تطبيقية في معمل السجاد الميكانيكي - نزار عبدالمجيد البرواري; محمد خليل ابراهيم القيسي (PROSPECTIVE RESEARCHES, 2023)
Recently, Quality Conception takes an increased importance, because of business environmental complexes and the appearance of, economic parties and globalization, as a controlling and agreements such as world of this system, organizations and countries which needs concentration on quality as abasement for competitive advantage should help the organization in this hung current flow of services and goods. Therefore, there is a need to fix a standard to be the appearance of quality suppliers and customers which leads to the appearance of quality management systems ISO 9000. ISO 9000 is a family of international standards which describe a basic set of elements from which a quality management system can be evolved, Hence this family has the challenges priority that face the organizations in our Iraqi environment in special, so the necessity calls for study and analysis of the dimensions of international standard dimensions (ISO 9001) from one side and, to concentrate on weakness and strength points from another side in the response to the study sample in mechanic carpet factory.